2017
DOI: 10.1155/2017/9125493
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Management of a Substantial Pelvic Aneurysmatic Bone Cyst Including the Off-Label Use of Denosumab in a 35-Year-Old Female Patient

Abstract: Aneurysmal bone cysts (ABC) are benign bone tumors, which are highly vascularized. The main course of treatment is curettage followed by bone grafting or cement insertion. Still recurrence remains a main problem for patients. Denosumab is a monoclonal antibody, which acts as an inhibitor of the RANK/RANKL pathway, diminishing bone turnover. Recent case reports have shown that Denosumab can be a promising therapeutic agent for people suffering from therapy-resistant ABC. We report the case of a 35-year-old fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 29 publications
0
22
0
8
Order By: Relevance
“…In 2017, Ntalos et al [24] (case report from Germany) reported a 35-year-old female patient with a primary ABC involving the pelvis that was not amenable to surgical intervention. The patient complained of right-sided pain and gluteal swelling.…”
Section: Reviewmentioning
confidence: 99%
“…In 2017, Ntalos et al [24] (case report from Germany) reported a 35-year-old female patient with a primary ABC involving the pelvis that was not amenable to surgical intervention. The patient complained of right-sided pain and gluteal swelling.…”
Section: Reviewmentioning
confidence: 99%
“…To our best knowledge, 2 case series (with 9 patients each) have previously been published [18][19][20] with an additional 11 cases having been published as individual case reports [20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…Doses of denosumab ranged from 1.6 mg/kg monthly to 70 mg/m 2 monthly for a duration of 4 months to 2 years. One patient developed transient hypocalcemia during the course of treatment (6,12,(16)(17)(18).…”
Section: Discussionmentioning
confidence: 99%
“…The reports on the use of denosumab for ABCs in children are currently limited to case reports and small series, highlighting mainly the beneficial effects on lesion growth, associated bone pain and facilitation of subsequent surgeries (9,10). Some of these reports have already described well known side effects associated with denosumab, such as hypocalcemia when treatment is initiated, and rebound hypercalcemia at the treatment discontinuation (11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%